Ważniejsze wyniki spisów powszechnych 2002 w województwie dolnośląskim - Polak, Helena (Most Important Results from the National Census 2002 in Lower Silesian Voivodeship, 2006)
"In this publication the most important results gained from the National Census and the National Agricultural Census have been presented. The aim of the article was to introduce the reader to the basic information on Lower Silesian Voivodeship, i.e.: population by age, marital status, education, professional activity, disability, declared nationality, households and their structure, housing conditions, area of arable farms, headage of farm animals, and technical infrastructure.In order to make the depiction of situation in the voivodeship more complete the information on Lower Silesian Voivodeship was referred to the information on the country and other voivodeships."
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1140, s. 136-145